Social and solidarity economy: Between emancipation and reproduction - Joana S. Marques (United Nations Research Institute for Social Development (UNRISD), 2014)
Social and solidarity economy (SSE) is increasingly attracting the attention of policy makers, practitioners and social scientists worldwide. For some, it contributes to social cohesion by addressing state and market failures; for others, it provides an alternative model to current neoliberal development patterns; for its critics, it is just another facet of contemporary capitalism. The purpose of this paper is to critically examine SSE in light of these different trends, while also addressing the issue of market and state relations. The paper presents a theoretical reflection and an empirical comparative analysis of the cases of Brazil and Portugal, which illustrate the different trends and challenges that SSE faces. While the fundamental question of whether SSE is a product and instrument of the capitalist system or represents an emancipatory alternative remains unresolved, findings from Brazil and Portugal show how SSE can be envisaged in three main ways: as a market-oriented initiative, as a method of local development or as a conscious project of social transformation.
Keywords: 330